The Role of Islamic Education in Enhancing 21st Century Skills: Focusing on Critical Thinking, Creativity, and Collaboration in Digital Era - Wahab, Abdul; Ihsan, Mahlil; Dena Juang, Femi; Saldiana, Rina; Irfan Saepul Milah, Asep (Lafadz Jaya Publisher, 2025)
This article aims to explore how Islamic education can contribute to enhancing 21st-century skills through the principles of Islamic teachings. The objective of this research is to identify how the values contained in Islamic education can support the development of the skills needed by the youth of the 21st century in digital era, such as critical thinking in problem-solving, creativity in innovation, and collaboration in working with others. This research employs a qualitative approach with a literature study method to analyze various literatures related to Islamic education and 21st-century skills. Data sources are drawn from articles, books, and Islamic education curriculum documents that integrate 21st-century skills. In the data analysis, an inductive approach is used to explore the relationship between the principles of Islamic teachings and the skills required in the modern world. The findings of this research show that Islamic education can provide a strong foundation for the development of 21st-century skills by integrating the moral and ethical principles of Islam that support character development. For example, teachings on reflective and evaluative thinking can encourage the development of critical thinking skills, while collaboration in social and religious contexts strengthens teamwork skills. The implications of these findings highlight the importance of designing an Islamic education curriculum that can effectively integrate 21st-century skills. This approach is expected to enhance the quality of Islamic education, making it more relevant to the demands of the times and preparing students to face global challenges.